(3EQTGO GdeHJOi hJPcQI GdefJgi (B( (3aj GdbQGAGJ GdYTQ HGdMLGR hGdTGe hGdYQGb (B)s - (3CHh GdYR eMeO Hf GdMSjf Hf Ydj Hf HfOGQ GdhGSWis; (3GdbdGfSj , CHh GdYR,J (B521 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf gPG cJGH CPcQ ajg GdbQGAI HGdMLGR hGdTGe hGdYQGb , hHjGf ENJdGage ai GdgeR s
(3BNQgG (B:s
(3ShQI GdENdGU hba MeRI HGdhGh eY EScGf GdaGA BNQ GdNdGa Je HMeO Gddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B101 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B236s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs